Effect of moisture on the heat capacity and the regeneration heat required for CO2 capture process using PEI impregnated mesoporous precipitated silica. Issue 1 (14th April 2014) - Quang, Dang Viet; Dindi, Abdallah; Rayer, Aravind V; Hadri, Nabil El; Abdulkadir, Abdurahim; Abu‐Zahra, Mohammad R.M.
Abstract In this study, we report the effect of the moisture of polyethylenimine (PEI) impregnated mesoporous precipitated silica used for CO2 adsorption on the heat capacity and the heat required to regenerate the adsorbent. The results indicate that the heat capacity of the absorbent increases as its moisture content increases. The increase in moisture results in the rise of the vaporization heat of water and the elevated heat capacity results in higher sensible heat. For these reasons, the total regeneration heat required for CO2 capture process increases significantly. The adsorbent has a maximum CO2 adsorption capacity at 75 °C. CO2 capture process using PEI impregnated mesoporous precipitated silica requires a minimum energy to regenerate the adsorbent; it reduces 46% of the energy compared to a process using an aqueous MEA 30 wt%, as the process operates at 75 °C.